Effectiveness of an Instructional Program on Behaviors of Parents Toward Children with Attention Deficit Hyperactivity Disorder in Autism Centers at Baghdad City - Safaa Razzaq Arrar, Saud Hassoon Khudhair (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the effectiveness of instructional program on behaviors of parents toward children with Attention Deficit Hyperactivity Disorder. Methodology: A quasi-experimental study was conducted that included (120) deliberate samples of parents selected from eight autism centers according to the study criteria (60) parents in the centers (Al-Safa, Al-Marwa, Basmat Amal, Al-Tahadi), and (60) parents in the centers (Al-Rami, Al-Rahman, Al-Takhassusi, Al-Saeeda Family. The samples were divided into two groups (60) parents (study group) who participated in the instructional program and (60) parents (control group) who did not participate in the program. The groups are almost identical in their properties. The instructional program was implemented in four steps, the first step (pre-test) is to assess parents’ behaviors towards children with ADHD before implementing the program, and the second step is to implement the program and then two tests and the time period between the first and second test is two weeks. The validity and reliability of the questionnaire were determined by a group of experts and through a pilot study of ten parents. Descriptive and inferential statistics were used to analyze the data. Results: The results of the study indicated that the general evaluation of the parents’ behaviors about ADHD for the study sample before implementing the program was a lack of basic behaviors about ADHD, but after implementing the program the result was: The study indicated a high effectiveness in the behaviors of the parents Matters between the study group as indicated by the high significance associated with the “Greenhouse-Geisser” correction at p-value = 0.001. A significant difference was found for the study group on the first and second pretest and posttest over time, compared with the control group.